Comparative Analysis of External Lightning Protection Systems Using Protective Angle and Rolling Sphere Method in Areas That Have High Lightning Intensity - Gilang Indrianto Pramono; Mohamad Rodhi Faiz; Langlang Gumilar; Sujito Sujito (Frontier Energy System and Power Engineering, 2023)
Indonesia is a tropical country with a geographical condition where 71% of its area is water. This is what coueses Indonesia is considered a country with a high density of lightning strikes. This results in buildings in Indonesia being at a high risk of damage caused by lightning strikes. According to data from BMKG, the city of Malang has a high lightning intensity, with 108 thunderstorm days per year, posing a serious threat to the Electrical Engineering Building of the Faculty of Engineering at the University of Malang. Considering the building's age and expansion on the building's side, it is necessary to evaluate the lightning protection system to determine whether the existing system is still working effectively and efficiently. Improving the system's performance against lightning disturbances can be done by analyzing the previous external lightning protection system and then evaluating it using the angle of protection and rolling sphere methods. The analysis and evaluation of the external protection system are based on PUIPP, PUIL, SNI, and IEEE standards.